2002
DOI: 10.1046/j.1365-2664.2002.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale habitat selection by agricultural steppe birds in Spain: identifying species–habitat responses using generalized additive models

Abstract: Summary1. Predictive models of species' distributions are used increasingly in ecological studies investigating features as varied as biodiversity, habitat selection and interspecific competition. In a pilot study, we based a successful model for the great bustard Otis tarda on advanced very high resolution radiometer (AVHRR) satellite data, which offer attractive predictor variables because of the global coverage, high temporal frequency of overpasses and low cost. We wished to assess whether the approach cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
150
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(161 citation statements)
references
References 33 publications
9
150
1
1
Order By: Relevance
“…Contrary to other studies (Suarez-Seoane et al 2002;Silva et al 2004;Osborne and Suarez-Seoane 2007;Silva et al 2010), we found no effect of proximity to anthropogenic infrastructures on the occurrence of little bustards at the landscape scale. However, at the smaller scale, displaying males located at points further from roads, suggesting that when not constrained by the availability of pastures and new fallows, roads were avoided.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Contrary to other studies (Suarez-Seoane et al 2002;Silva et al 2004;Osborne and Suarez-Seoane 2007;Silva et al 2010), we found no effect of proximity to anthropogenic infrastructures on the occurrence of little bustards at the landscape scale. However, at the smaller scale, displaying males located at points further from roads, suggesting that when not constrained by the availability of pastures and new fallows, roads were avoided.…”
Section: Discussioncontrasting
confidence: 56%
“…These land-uses, associated with low-intensity agro-pastoral activities, are rapidly disappearing from most of the Palaearctic but still occur locally in southern Mediterranean regions and are well known as a suitable habitat for the little bustard in Iberia (Martinez 1994;Salamolard and Moreau 1999;Suarez-Seoane et al 2002) and southern France (Wolff et al 2001). A strong preference for high heterogeneity of land-use substrates was also evident in the non-spatial model but not in that incorporating spatial autocorrelation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The Advanced Very High Resolution Radiometer (AVHRR) from the National Oceanic and Atmospheric Administration (NOAA) was applied in 22 studies; six times it was used together with other satellite sensors. These coarseresolution imageries were often used in large-scale studies covering entire or large parts of countries (Wallin et al 1992, Suarez-Seoane et al 2002, Venier et al 2004, continents (O'Connor et al 1996, Johnson et al 1998, Roshier et al 2001, HAcevedo and Currie 2003 or the ocean (Haney and McGillivary 1985a, Jouventin et al 1994, Huettmann and Diamond 2001. With the help of NOAA AVHRR imagery often the actual or integrated normalized difference vegetation index (NDVI) was calculated to produce maps of primary production or to detect green biomass (Wallin et al 1992, Andries et al 1994, Hepinstall and Sader 1997, Verlinden and Masogo 1997, Osborne et al 2001, Saveraid et al 2001, in order to detect habitat change (Sader et al 1991, Debinski et al 2000, to map wetland distribution (Roshier et al 2001) or to explain the distribution of centres of bird endemism (Johnson et al 1998).…”
Section: Satellite Imagerymentioning
confidence: 99%
“…Recent developments in geographic information systems (GIS) and habitat modelling provide an ideal methodological framework in which high-resolution analyses of habitat attributes can be performed at the landscape level. Models allow gaining insights into the environmental variables (such as biotic, physical, climatic or human-induced habitat conditions) acting on species survival by comparing current species distribution with the optimal values for each variable (Guisan and Zimmermann 2000;Osborne et al 2001;Suárez-Seoane et al 2002). The output of the models is a habitat suitability index (HSI) which ranges from 0 (low quality) to 1 (high quality).…”
Section: Introductionmentioning
confidence: 99%